2011
DOI: 10.1002/jcp.22542
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of intracellular glutathione affects adipogenesis in 3T3‐L1 cells

Abstract: Impairment of redox homeostasis has been extensively associated with obesity, as a consequence of the chronic inflammatory state present in overweight subjects. Deregulation of glutathione (GSH), the most important non-enzymatic intracellular anti-oxidant, induces insulin resistance in mature adipocytes, but data are lacking about its effects on adipogenesis. In this report we demonstrate that during adipogenesis of 3T3-L1 cells the GSH/GSSG ratio decreases, shifting redox status towards oxidizing conditions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 57 publications
(67 reference statements)
4
60
0
Order By: Relevance
“…PGC-1a and p53 siRNA oligonucleotides are reported in Table 1. ROS/RNS levels were assayed by means of DCF-DA staining as previously reported (44).…”
Section: Cell Cultures Transfections and Ros/rns Assaymentioning
confidence: 99%
“…PGC-1a and p53 siRNA oligonucleotides are reported in Table 1. ROS/RNS levels were assayed by means of DCF-DA staining as previously reported (44).…”
Section: Cell Cultures Transfections and Ros/rns Assaymentioning
confidence: 99%
“…These pathways and regulators include glutathione (Vigilanza et al, 2010), the Janus kinase-signal transducer and activator of transcription 3 (JAK-STAT3) pathway (Zhang et al, 2011), SMAD signalling (Marchildon et al, 2010;Tan et al, 2011), ribosomal protein S6 kinase 1 (S6K1) (Carnevalli et al, 2010) and components of the insulin signalling cascade, such as AKT ) and a newly discovered regulator of this pathway, inositol pyrophosphate (Chakraborty et al, 2010). New transcriptional regulators of stem cell fate that are controlled by these pathways also continue to be identified.…”
Section: Signals To Differentiatementioning
confidence: 99%
“…(33). Another independent study showed that ROS facilitate adipocyte differentiation in 3T3-L1 cells again by accelerating the MCE phase and activating C/EBPβ, whereas exposure to broadly-acting antioxidants such as N-acetyl cysteine greatly inhibited adipogenesis (9).…”
Section: Discussionmentioning
confidence: 99%